HUBUNGAN ANTARA PENGETAHUAN HUKUM DENGAN SIKAP ANTIKORUPSI SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN KELAS X SMK NEGERI 2 KARANGANYAR - Wati, Endang; ., Winarno; Rejekiningsih, Triana (Educitizen, 2018)
ABSTRACTThe objective of this research is to investigate whether or not there is a significant relationship between knowledge of the law and anticorruption attitude in the 10th graders of SMK Negeri 2 Karanganyar. This research employed a descriptive quantitative method that was correlational in nature. The result of research showed that there was a positive and significant relationship between knowledge of the law and anticorruption attitude, in the 10th graders of SMA Negeri 2 Karanganyar. The result of data analysis obtained rxy = 0.517 at significance level of 5% with N = 132, r table = 0.170 so that rstatistic> rtable 0.517 > 0.170, so that Ha was supported and Ho was not supported meaning that there was a positive relationship between X and Y variables. Meanwhile, tstatistic = 6.885 at significance level of 5% with df (n-2) = 132 ? 2 = 130 and tstatistic = 1.656 so that tstatistic> ttable yaitu 6.885 > 1.656, so that X variable contributed significantly to Y variable. In addition, the size of the contribution of X variable to Y variable was 26.73% and the rest of 73.27% was affected by other factor. The simple linear regression equation obtained was Y = 47.988 + 0.396 X, so the regression equation obtained represented that every one unit increase in X variable, it was followed with the increase by 0.396 point in Y variable. The conclusion of research was there was a significant relationship between knowledge of the law about corruption and anticorruption attitude in the 10th graders of SMK Negeri 2 Karanganyar. Keywords: Knowledge of the law, anticorruption attitude